Economic Analysis and Carrying Capacity of the Bontang Mangrove Park Ecotourism Area Kutai National Park in East Kalimantan - Rina Marsela Safri; Siti Amalia; Auliansyah Auliansyah (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
The Bontang Mangrove Park (BMP) area is an ecotourism area within the Kutai National Park, East Kalimantan. As an ecotourism area, research was conducted with the aim of calculating the economic value, carrying capacity of the area, and seeing how BMP contributes economically to the surrounding population. The objectives are answered with a qualitative descriptive approach and a quantitative descriptive approach, using the Travel Cost Method analysis tool based on the visitor's origin zone and carrying capacity analysis. Based on the results of the analysis, the economic value of BMP reaches IDR 6,471,315,944/year. The carrying capacity of BMP for mangrove tracking tourism activities is 280 people/day, and boating tourism is 90 people/day. Economic contribution to people's income in October IDR 10,277,400, November and December IDR 13,477,400 then the overall result of the economic contribution for 3 months becomes IDR 117,122,000.